PHARMACOGENETICS OF ANESTHESIOLOGICAL SUPPORT - О. Скавінська; Л. Фіщук; Ю. Чернявська; В. Похилько; О. Євсеєнкова; З. Россоха (Неонатологія, хірургія та перинатальна медицина, 2024)
Pharmacogenetics studies the relationship between a person’s individual genetic characteristics and the human body’s response to the action of various drugs, particularly the occurrence of undesirable side eff ects. Thanks to the development of the latest technologies and methods, this branch of medical genetics and clinical pharmacology is developing very actively. Data are being accumulated, special databases are being created with the aim of creating individual genetic passports in the future, which will allow the selection of personalized treatment schemes. Anesthesiology is a special area of pharmacogenetic research because, more than any other medical specialty, it is characterized by polypharmacy-the simultaneous or sequential administration of many drugs. The same dose of a drug may be inadequate for some patients and may be life-threatening or cause unwanted side eff ects for others. Today, information about genetic factors is being used by clinicians to prescribe drugs to tailor drug therapy to a patient’s genome. In anesthesiology, the principles of pharmacogenetics have been explained for neuromuscular blocking agents, opioid metabolism, different types of anesthetics, and postoperative nausea and vomiting. On the other hand, a large number of anesthetics have a narrow therapeutic index. This review summarizes the most recent data from the scientifi c literature on the pharmacogenetics of diff erent types of anesthetics. Inhalational anesthetics are halogenated derivatives of methyl ethyl ether, the exact mechanism of action of which is not yet fully understood. One of the rare but very serious side eff ects of all halogenated anesthetics is malignant hyperthermia, a genetically determined autosomal dominant disorder that manifests as a hypermetabolic response to drug administration. The dosage of intravenous anesthetics should also be carefully determined, taking into account the patient’s age, cardiovascular, hepatic, and renal status, concomitant drug therapy, and genetic factors. Ontogeny and genetic variability of drug-metabolizing enzymes are interrelated because genetic variability in drug-metabolizing enzyme expression cannot be assessed until the required protein is suffi ciently expressed. Pharmacogenetic variants may contribute to unpredictable drug exposure at the same weight- based drug dose. There are a number of potentially clinically applicable pharmacogenetic data in newborns, but more research is needed to confi rm these fi ndings and understand how to incorporate them into clinical care. The selection of drugs and dosing regimens based on a patient’s pharmacogenomic profi le may be an important part of the future of medicine. Personalized treatment based on the specifi c variants in the genome will ultimately reduce the incidence of side eff ects and length of hospital stay for patients and save healthcare costs. Although pharmacogenomics and its application in clinical practice are still in their infancy, different variants and their implications for many clinical areas, including anesthesiology, are emerging every day.